(untitled) (Acta Scientiarum. Language and Culture, 2019)
Ursula K. Le Guin’s The dispossessed (1974) has been read from a multiplicity of angles that mostly vary from focusing on the characters to highlighting the anarchist ideology that the story preaches. In this article, we promote a distinct analysis, which, despite also approaching the ideological themes in the novel, centres on the use the author makes of glossopoesis (creation of artificial languages) through Pravic, Iotic and Niotic. Bourdieu (1991), Freedman (2000), Conley and Cain (2006), Edward James (2003) and Ken Macleod (2003) critically motivate our discussion. As a result, we demonstrate how glossopoesis plays a significant representational role in the plot as a secondary narrative framework intended to communicate the author’s beliefs both on language and politics.